2018
DOI: 10.1001/jamasurg.2017.3821
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Military Use of Tranexamic Acid and Associated Thromboembolic Events

Abstract: Military medical personnel decreased missed opportunities to appropriately use TXA but also increased overuse. In addition, TXA administration was an independent risk factor for venous thromboembolism. A reevaluation of the use of TXA in combat casualties should be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 15 publications
1
70
1
2
Order By: Relevance
“…HR, hazard ratio; CI, confidence interval; HF, hyperfibrinolysis; SBP, systolic blood pressure;ISS, injury severity score; PT_INR, prothrombin time and international normalized ratio. (2020) 10:6980 | https://doi.org/10.1038/s41598-020-63724-y www.nature.com/scientificreports www.nature.com/scientificreports/ enhanced the occurrence of thrombotic events [30][31][32] . We believe that FIBTEM HF may have potential for use in selective TXA administration; however, additional research on the topic is needed.…”
Section: Discussionmentioning
confidence: 99%
“…HR, hazard ratio; CI, confidence interval; HF, hyperfibrinolysis; SBP, systolic blood pressure;ISS, injury severity score; PT_INR, prothrombin time and international normalized ratio. (2020) 10:6980 | https://doi.org/10.1038/s41598-020-63724-y www.nature.com/scientificreports www.nature.com/scientificreports/ enhanced the occurrence of thrombotic events [30][31][32] . We believe that FIBTEM HF may have potential for use in selective TXA administration; however, additional research on the topic is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, TXA should only be started later than 3 h after injury if signs of trauma-induced coagulopathy (A5 EX < 35 mm or FIBTEM flat-line [CT FIB > 600 s]) or hyperfibrinolysis (EXTEM or FIBTEM maximum lysis [ML] ≥ 5% within 60 min) are present [105,[145][146][147]. However, it is still under debate whether prophylactic or therapeutic administration of TXA should be performed in hospitals with access to viscoelastic testing [145][146][147][148][149][150][151][152][153][154][155]. Physiologic fibrinolysis and fibrinolysis shutdown are defined in ROTEM as an EXTEM LI60 82-97.9% and ≥ 98%, respectively [156].…”
Section: In Trauma and Orthopedic Surgerymentioning
confidence: 99%
“…While some studies have not identified an increase in incidence of VTE associated with TXA, others have found TXA to be an independent risk factor for increased incidence of VTE. 11,12,14,[17][18][19] Thus, there is a need to continue to further evaluate the safety of TXA use within the hospital trauma setting.…”
Section: Introductionmentioning
confidence: 99%